A phase 2 study of brentuximab vedotin in patients with CD30-positive advanced systemic mastocytosis - Gotlib, Jason (Blood Adv, 2019)
There is an unmet need for effective therapies for advanced systemic mastocytosis (advSM). CD30 is expressed on the surface of neoplastic mast cells (MC) in more than 50% of patients with advSM. Brentuximab vedotin (BV) is a CD30-directed antibody-drug conjugate with preclinical evidence supporting both an antineoplastic effect and an attenuation of immunoglobulin E-associated mediator release. These observations are the basis for this phase 2 trial of BV monotherapy (1.8 mg/kg IV every 3 weeks up to 8 cycles) in patients with CD30-positive advSM. The primary objective was to determine the efficacy of BV according to International Working Group-Myeloproliferative Neoplasms Research and Treatment-European Competence Network on Mastocytosis (IWG-MRT-ECNM) response criteria. Secondary objectives included evaluation of safety, changes in bone marrow (BM) MC burden, serum tryptase level, flow cytometric quantification of MC surface expression of CD30, and self-reported symptom burden. The trial enrolled 10 patients with a diagnosis of CD30(+) advSM (aggressive SM, SM with an associated hematologic neoplasm [SM-AHN], or mast cell leukemia [MCL]) with 1 or more signs of SM-related organ damage. According to IWG-MRT-ECNM criteria, none of the patients demonstrated better than stable disease with BV. In addition, there were no significant reductions in BM MC burden, serum tryptase levels, or MC surface expression of CD30. Self-reported symptom scores showed no durable improvement with BV treatment. We conclude that BV is not active as a single agent in CD30(+) advSM. This trial was registered at www.clinicaltrials.gov as #NCT01807598.